Aktivitas Anti Trombotik dari Genus Curcuma : Kajian Sistematik - Sandhori, Fajar Jamaluddin; Kusumawati, Idha; Samirah, Samirah; Rullyansyah, Subhan; Ramadhani, Firmansyah Ardian; Prasetyawan, Hanif Rifqi; Warsito, Mega Ferdina (Journal of Islamic Medicine, 2024)
Background : The Curcuma genus has various pharmacological activities, one of these is antithrombotic activity by preventing thrombus formation. Some of its chemical contents are also known to inhibit thrombus formation including curcumin, bisdemethoxycurcumin, ar-turmerone, and xanthorrizhol compounds. Antithrombotic drugs are used for the prevention and treatment of thrombosis whose mechanisms are divided into anticoagulants, thrombolytics, and antiplatelets. Objective: This review article discusses the potential of Curcuma genus as antithrombotic, including anticoagulant, antiplatelet, and thrombolytic, Methods: This study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method using four databases : PubMed, ScienceDirect, Scopus, and Google Scholar from July to December 2023. The inclusion criteria used were articles on antithrombotic activity, including anticoagulants, antiplatelets, and thrombolytics from the genus Curcuma. Results: The number of articles obtained from four databases was 3413 articles. Furthermore, based on the results of filtering duplicate articles from all databases, 2771 articles were selected and then continued with screening based on inclusion and exclusion criteria until 15 articles were selected as material for systematic review. Conclusion: Curcuma species that have potential as antithrombotic are Curcuma longa, Curcuma zedoaria Rosc., Curcuma amada, Curcuma caesia, Curcuma aeruginosa, Curcuma latifolia, Curcuma aromatica Salisb, Curcuma wenyujin, and Curcuma xanthorrhiza